Edukasi Manajemen Risiko Musculoskeletal Disorders (MSDs) pada Pekerja Pengelasan (Welding) di PT. Catra Dharma Kara - Damayanti, Dinda Camela; Hasta, Arys (Rena Cipta Mandiri, 2025)
Musculoskeletal Disorders (MSDs) are one of the health problems often experienced by welding operators in the industry, especially due to unergonomic working postures, long working durations, and repetitive movements. This community service was carried out at PT. Catra Dharma Kara with the aim of increasing workers' understanding of MSDs risk management. The Service Learning (SL) approach was used through observation, interview and lecture methods. Pre-test and Post-test were used to evaluate workers' understanding before and after education. The results showed a significant increase in understanding of MSDs risk management, with a change from 10% in the pre-test to 100% in the post-test.